Implementation of the PAI Supervisor Work Program in Improving the Quality of PAI Teachers in Jombang Regency - Zafnimar Khusnul Fahmi; Zifa Zahiyah Azida Fauzi (Jawda: Journal of Islamic Education Management, 2026)
The background for this study is rooted in the close relationship between the quality improvement of islamic education teachers and the strategic work programs designed by supervisors. This research specifically aimed to ascertain the implementation effectiveness of PAI supervisor work programs in enhancing PAI teacher quality within Jombang regency. The study employed utilized a qualitative case study approach, with primary data collected through interviews and observation to detail the specific programs and evaluate their impact on teacher competency. The results revealed that the supervisor coaching programs notably through PAI teacher working group training, workshops, and continuous mentoring contribute significantly to strengthening teachers' Ngopai pedagogic and professional competence. However, program optimization faces several challenges, including an unfavorable supervisor-to-teacher ratio, various geographical constraints, and the teachers' limited mastery of current technology. In conclusion, this evidence underscores the critical importance of fostering robust collaboration among all educational stakeholders and the necessity of formulating more structured and supportive policies to guarantee the sustainable, long-term improvement of PAI teacher quality.